Penerapan UML dan Metode Waterfall pada Sistem Pelacakan Sertifikat Tanah Berbasis Web - Hadi, Harry Setya; Yahyan, Wahyuni; Sabriani, Mutia (Journal of Informatics Management and Information Technology, 2025)
Land certificate administration services at the ATR/BPN Mentawai Islands Office still face various obstacles, especially in terms of transparency and tracking of the application process which is carried out manually. This can cause uncertainty of information for the public. To overcome these problems, a web-based land certificate administration tracking information system was designed that can be accessed online. This system aims to make it easier for the public to monitor the progress of land certificate applications efficiently, quickly, and transparently.The system design was carried out using the System Development Life Cycle (SDLC) Waterfall model approach, which consists of the stages of needs analysis, design, implementation, testing, and maintenance. In system modeling, Unified Modeling Language (UML) tools were used, including use case diagrams, activity diagrams, class diagrams, and sequence diagrams. Sequence diagrams are used to describe the interactions between objects in the system, such as the flow of tracking certificate applications between users and the system.The system was developed using the PHP programming language on the server side and MariaDB as a database management system. The results of this study are in the form of a web application that can be used by the public and officers to track and manage land certificate applications digitally, effectively, and in a structured manner.